Capturing Students’ Creative Thinking: An Analysis of Middle Schoolers’ Processes in Solving Mathematical Reasoning Problems - Rohati Rohati; Marlina Marlina; Ade Kumalasari; Sri Winarni (MASI Mandiri Edukasi, 2026)
Schools play a critical role in enabling students to discover, develop, and express their creative potential. However, instructional practices that explicitly promote students’ creative thinking skills in mathematics learning remain limited. Therefore, this study aims to examine and describe the creative thinking processes of junior high school students in solving mathematical reasoning problems. This study employed a qualitative case study design involving 35 eighth-grade students. A mathematical reasoning test was administered to identify students’ levels of creative thinking. Based on the results, four students representing different categories of creative thinking (imitative, routine, creative, and very creative) were purposively selected as research subjects. Data were collected through students’ written work, in-depth interviews, and document analysis. The findings indicate that each category demonstrates distinctive characteristics in terms of problem-solving strategies, flexibility of ideas, and originality in constructing solutions. Students in the higher creative categories tended to generate multiple strategies and more original solution processes. These findings emphasize the importance of designing mathematics learning activities that encourage exploration of diverse strategies, idea generation, and reflective thinking.